Elimination of burr formation during end milling of Polymethyl Methacrylate (PMMA) through high speed machining - Amin, A. K. M. Nurul; Syaban, M.; Mahmud, Md. Asif (IIUM Press, 2011)
A burr is a raised edge or small pieces of material remaining attached to a workpiece after it has undergone machining. The Burr, Edge and Surface Technology (BEST) Division, the Society of Manufacturing Engineers defines a burr as “an undesirable projection of material that results from cutting, forming, blanking or shearing operation [1]. The first stage, chip formed in front of the cutting tool with a positive shear angle, φ. The plastic zone around the primary shear zone is extended towards the work edge when cutting tool advance toward the work edge.There are four basic types of burr that have been defined by researchers which are: poisson, roll-over, tear burr and cut-off burr [2-3]. The four specific types of burr are: Roughness refer to the small, finely spaced deviations from the nominal surface, which is determined by the material characteristics and the process that formed the surface [4]. The theoretical surface roughness, can be estimated using the following equation [5] = / 32(R ± / π) (1) Where is the surface roughness, is the number of teeth on the cutter, R is the radius of the cutter, is the feed per revolution and the (+) sign refers to up-milling and the (-) sign refers to down milling.The above equation does not consider many factors that in reality can affect the surface roughness. For this reason the surface roughness will generally be higher than that predicted by Eq. (1). Statistical models that include such factors as depth of cut and spindle speed in addition to feed rate have been developed [6].